High-zirconium brick as well as preparation process and application thereof

By preparing high zirconium bricks, the problems of high zirconia series of melt-cast refractory materials are solved, and high efficiency and durable refractory materials for glass kilns are realized.

CN119462178AInactive Publication Date: 2025-02-18ZHENGZHOU FANGMING HIGH TEMPERATURE CERAMIC NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411611037.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high zirconia series of melt-cast refractory materials have problems such as high manufacturing costs and poor thermal impact performance, which limits their application in glass kilns.

Method used

A high zirconium brick is proposed, which includes 65% to 99% zirconium dioxide, as well as the synthesis of aluminum oxide, yttrium oxide, titanium oxide, magnesium oxide, calcium oxide, silicon oxide, etc., through a specific preparation process, including high-temperature reaction, Powder grinding, adhesive addition and pressing molding to form high zirconium bricks with uniform density and uniform distribution of elements.

Benefits of technology

It improves the optimal service life and cost-effectiveness of high-zirconium bricks, ensures that the product has uniform density, no pores, excellent thermal shock resistance and strong corrosion resistance, and is suitable for long-term high-temperature environments above 1550℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462178A_ABST
    Figure CN119462178A_ABST
Patent Text Reader

Abstract

The invention discloses a high-zirconium brick as well as a preparation process and application thereof. The high-zirconium brick comprises the following components in percentage by weight: 65-99% of zirconium dioxide, 0.5-30.5% of aluminum oxide and 0.5-4.5% of yttrium oxide, titanium oxide, magnesium oxide, calcium oxide and silicon oxide in total. According to the method, heating and annealing cooling are controlled in a curve temperature control mode, all elements in the prepared high-zirconium brick are integrally uniform and free of segregation, the whole body density of the product is uniform and consistent, the defects of needle-shaped air holes, bubble retention, surface holes and the like do not exist, and the high-zirconium brick product prepared through the technological method is short in delivery cycle and can be produced in a customized mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to materials for glass kilns, specifically a high-zirconium brick and its preparation process and application. Background Art Materials used in glass kilns are roughly divided into sintered materials and cast materials. Although the preparation process of sintered materials is relatively simple, due to their generally high porosity (about 10-30%), they are prone to problems such as bubbles and aggregate separation when used in glass kilns, resulting in defects such as bubbles and sand particles in glass products. Therefore, they are not suitable for key parts of glass kilns that come into contact with high-temperature liquids. In particular, for high-zirconia sintered materials that have been added with stabilizers such as Y2O3, MgO, and CaO to prevent the monoclinic and tetragonal phase transition of zirconium oxide between 900°C and 1200°C, the stabilizers will dissolve in the glass liquid in the high-temperature environment of the glass kiln, causing the stable zirconium oxide to transform into an unstable state. The phase transition continues, making the material structure fragile, and also causing defects such as sand particles in the glass. Therefore, this type of material is also not suitable for glass kilns.

[0003] Relatively speaking, fused-cast refractory materials are cast after melting the raw materials in an electric furnace, fully homogenizing them, and then cooling and solidifying them. The products obtained have dense structure and developed crystallization, which are more suitable for the use environment of glass kilns. Among them, fused-cast materials with high zirconium oxide content have become the preferred materials in glass melting furnaces due to their excellent corrosion resistance. This type of material is mainly divided into two categories: one is the Al2O3-ZrO2-SiO2 series fused-cast refractory materials with a zirconium oxide content between 33% and 41%; the other is the high zirconium oxide content series fused-cast refractory materials with a zirconium oxide content of up to 80% to 95%. The latter has been widely used in high-quality glass kilns in recent years because of its better corrosion resistance and low pollution to glass liquid.

[0004] However, the existing high zirconia series of refractory materials still have some defects. For example, due to the lower glass phase content than fused zirconium corundum (AZS), and the difference in cooling speed during the casting process, some materials will have annual ring-shaped structures with high porosity, which may lead to problems such as foaming. In addition, the high zirconia series of fused-cast refractory materials have low yield, long delivery cycle, and high price, which inhibit large-scale application. At the same time, factors such as poor thermal shock performance of fused-cast high-zirconium products and industry quality control capabilities cause large differences in application results. Therefore, the research and development and application of refractory materials for glass kilns still need continuous exploration and innovation to meet the glass industry's demand for high-quality, high-performance refractory materials. Summary of the invention

[0005] The purpose of the present application is to provide a high zirconium brick and its preparation process and application, so as to solve the problems of high manufacturing cost and poor thermal shock performance of the existing high zirconia series fused-cast refractory materials.

[0006] To achieve the above objectives, this application provides the following technical solutions: In the first aspect, the present application proposes a high-zirconium brick, which comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% alumina, and 0.5% to 4.5% by weight of yttrium oxide, titanium oxide, magnesium oxide, calcium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% magnesium oxide, and 0.5% to 4.5% by weight of yttrium oxide, titanium oxide, calcium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% calcium oxide, and 0.5% to 4.5% by weight of magnesium oxide, yttrium oxide, titanium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% chromium oxide, and 0.5% to 4.5% by weight of calcium oxide, magnesium oxide, yttrium oxide, titanium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% beryllium oxide, and 0.5% to 4.5% by weight of calcium oxide, magnesium oxide, yttrium oxide, titanium oxide, and silicon oxide.

[0007] In the second aspect, the present application proposes a preparation process of a high zirconium brick, the preparation process comprising the following steps: Step 1, weigh each component, mix them evenly, react at 1800°C to 3000°C for at least 45 minutes to form a molten liquid or solid phase structure, and cool to obtain a solid solution raw material; Step 2: Grind the solid solution raw material obtained in step 1 into a powder with a D50 value of 0.2 to 100 microns; Step 3: Add 0.1-5% organic binder or inorganic binder to the powder obtained in step 2 and mix well; Step 4: placing the powder obtained in step 3 in a mold, and pressing and molding at a pressure of not less than 500 tons for at least 15 seconds to obtain an initial embryo; Step 5: Heat the initial body obtained in step 4 from room temperature to 1600-1950°C by a temperature control heating device within at least 5 hours, and keep it at not less than 1600°C for at least 1 hour, and then cool it to room temperature within at least 5 hours to obtain a high zirconium brick body; Step 6: Grind and trim the brick body obtained in step 5 to obtain high-zirconium bricks.

[0008] As a specific scheme in the technical scheme of the present application, the mixed components in the step one are melted at 1800℃~3000℃ for at least 45 minutes, and cooled to obtain a solid solution raw material with uniformly distributed elements; or the mixed components are sintered at a high temperature liquid phase reaction at 1800℃~3000℃ for at least 60 minutes, and cooled to obtain a solid solution raw material with uniformly distributed elements.

[0009] As a specific solution in the technical solution of the present application, the organic binder in step three is selected from at least one of polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyacrylamide (PAM), polyimide adhesive, epoxy adhesive, phenolic resin adhesive, and urea-formaldehyde resin adhesive; the inorganic binder includes but is not limited to paraffin and wood ash.

[0010] As a specific solution in the technical solution of the present application, the powder obtained in step three is placed in a mold and is cold isostatically pressed at a pressure of 500-10,000 tons or is formed by a press at a pressure of not less than 500 tons for at least 15 seconds to obtain an initial embryo. The mold includes but is not limited to rubber, polyurethane, and metal molds.

[0011] As a specific solution in the technical solution of the present application, the temperature control and heating equipment in step five adopts a programmable temperature controller, and the starting temperature is set to room temperature, the heating rate is 320~390℃ / h, the heating time is at least 5h, the end temperature is 1600~1950℃, and the insulation time is at least 1h.

[0012] As a specific solution in the technical solution of this application, the temperature control heating equipment includes but is not limited to electric heating equipment, electromagnetic induction heating equipment, vacuum heating equipment, protective atmosphere heating equipment, gas heating equipment, plasma heating equipment, and microwave heating equipment.

[0013] As a specific solution in the technical solution of the present application, the cooling annealing in step five adopts a programmable temperature controller, sets the starting temperature to the furnace temperature, the cooling rate to 390-320°C / h, the cooling time to at least 5h, and the end temperature to room temperature.

[0014] On the third aspect, the present application proposes a high-zirconium brick for making various key ceramic products for glass kilns, including but not limited to: crucibles for special glass, high-zirconium ceramic stirring paddles, high-zirconium ceramic bricks, high-zirconium drawing crucibles, high-zirconium special-shaped accessories, and quartz furnaces.

[0015] Compared with the prior art, the beneficial effects of the present application are: according to the different types and composition requirements of glass liquid, reasonable raw materials of each component are selected to improve the optimal service life and cost performance of high zirconium brick products. In addition, the present application innovates the process route for preparing high zirconium bricks, and uses a curve temperature control method to control heating and annealing cooling through a programmable temperature controller. The elements in the prepared high zirconium bricks are uniform and segregated as a whole, and the density of the product is uniform throughout the body. There are no defects such as needle-shaped pores, bubble retention, and surface holes. There is no risk of local erosion and leakage. The high zirconium brick products prepared by the process method of the present application have a short delivery cycle and can be customized. Under high temperature conditions, the liquid phase solidification structure is stable, the bubble precipitation rate is extremely low, the erosion resistance is strong, the thermal shock resistance is excellent, and the thermal penetration temperature reduction performance is good, which ensures the safety of the kiln baking process, especially in a long-term working environment above 1550°C, compared with the fused AZS and fused 95 products, it has more obvious advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a process flow chart of the high zirconium conversion preparation process proposed in the embodiment of the present application; Figure 2 This is a microscope image of a high-zirconium brick sample proposed in the embodiment of this application; Figure 3 This is a practical diagram of thermal shock and thermal penetration of high-zirconium brick samples proposed in the embodiments of this application; Figure 4 This is the linear expansion rate test report of the high zirconium brick sample proposed in the embodiment of this application; Figure 5 This is the 1300°C bubble precipitation rate test report of the high zirconium brick sample proposed in the embodiment of this application; Figure 6 This is the 1500°C bubble precipitation rate test report of the high zirconium brick sample proposed in the embodiment of this application; Figure 7 The corrosion resistance test results of the crucible made of the high zirconium brick sample proposed in the embodiment of this application, the 41# zirconium corundum brick crucible and the 95# fused cast high zirconium brick DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be further clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] In order to solve the defects of the high zirconium oxide series refractory materials proposed in the background technology, this embodiment innovates the preparation process of high zirconium brick products. In addition, according to the different types and composition requirements of glass liquid, a variety of high zirconium brick composition is provided, aiming to improve the optimal service life and cost performance of high zirconium brick products. For example, the present application proposes that the high zirconium bricks include the following components by weight percentage: zirconium dioxide 65%~99%, aluminum oxide 0.5%~30.5%, yttrium oxide, titanium oxide, magnesium oxide, calcium oxide, silicon oxide weight sum of 0.5%~4.5%; or the high zirconium bricks include the following components by weight percentage: zirconium dioxide 65%~99%, magnesium oxide 0.5%~30.5%, yttrium oxide, titanium oxide, calcium oxide, silicon oxide weight sum of 0.5%~4.5%; or the high zirconium bricks include the following components by weight percentage: zirconium dioxide 65%~99%, calcium oxide 0. 5%~30.5%, the sum of the weight of magnesium oxide, yttrium oxide, titanium oxide and silicon oxide is 0.5%~4.5%; or the high zirconium brick comprises the following components by weight: zirconium dioxide 65%~99%, chromium oxide 0.5%~30.5%, and the sum of the weight of calcium oxide, magnesium oxide, yttrium oxide, titanium oxide and silicon oxide is 0.5%~4.5%; or the high zirconium brick comprises the following components by weight: zirconium dioxide 65%~99%, beryllium oxide 0.5%~30.5%, and the sum of the weight of calcium oxide, magnesium oxide, yttrium oxide, titanium oxide and silicon oxide is 0.5%~4.5%.

[0019] In order to avoid the defects of high zirconium brick products caused by the melting and casting process, such as element segregation, inability to eliminate pores and bubbles, uneven density, and surface microcracks, the present application improves the high zirconium brick preparation process. First, the components after uniform mixing are reacted at 1800-3000°C for at least 45 minutes to form a molten liquid or solid phase structure, and then cooled to obtain a uniformly distributed solid solution raw material. Specifically, the mixed components are melted at 1800-3000°C for at least 45 minutes, and then cooled to obtain a solid solution raw material with uniformly distributed elements; or the mixed components are sintered at a high temperature of 1800-3000°C for at least 6 minutes by liquid phase reaction. 0min, cooling to obtain a solid solution raw material with uniform distribution of elements; then grinding the obtained solid solution raw material into a powder with a D50 value of 0.2~100 microns; then adding 0.1~5% organic binder or inorganic binder and mixing evenly; then pressing and molding in a mold at a pressure of not less than 500 tons for at least 15 seconds to obtain an initial embryo; the initial embryo is heated from room temperature to 1600~1950℃ by a temperature control heating equipment within at least 5h, and maintained at not less than 1600℃ for at least 1h, and then cooled to room temperature within at least 5h to obtain a high zirconium brick embryo; grinding and trimming to obtain a high zirconium brick product.

[0020] In the specific implementation process of this application, the organic binder is selected from at least one of polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyacrylamide (PAM), polyimide adhesive, epoxy adhesive, phenolic resin adhesive, and urea-formaldehyde resin adhesive; the inorganic binder includes but is not limited to paraffin wax and wood ash. The powder after adding the binder is molded in the mold by cold isostatic pressing with a pressure of 500-10,000 tons or by a press at a pressure of not less than 500 tons, and is kept for at least 15 seconds to obtain the initial embryo. The mold includes various types, but is not limited to rubber rubber, polyurethane mold, and metal mold. The temperature control and heating equipment uses a programmable temperature controller, and the starting temperature is set to room temperature, the heating rate is 320~390℃ / h, the heating time is at least 5h, the end temperature is 1600~1950℃, and the insulation time is at least 1h. The cooling annealing adopts a programmable temperature controller, sets the starting temperature to the furnace temperature, the cooling rate to 390~320℃ / h, the cooling time to at least 5h, and the end temperature to room temperature. Temperature control and heating equipment include but are not limited to electric heating equipment, electromagnetic induction heating equipment, vacuum heating equipment, protective atmosphere heating equipment, gas heating equipment, plasma heating equipment, and microwave heating equipment. In the specific implementation process, the temperature control and heating equipment adopts a curve temperature control method to heat and cool down the initial embryo of the high zirconium brick, control the development of zirconium dioxide grains and anneal, and the high zirconium conversion product obtained has uniform and segregated elements as a whole, uniform density throughout the body, no defects such as needle-shaped pores, bubble retention, and surface holes, and no local erosion and leakage. Therefore, the high zirconium brick products prepared by the process method of this application have a short delivery cycle and can be customized. The high zirconium bricks prepared in this application are used to make various key ceramic products for glass kilns, including but not limited to: crucibles for special glass, high zirconium ceramic stirring paddles, high zirconium ceramic tiles, high zirconium drawing crucibles, high zirconium special-shaped accessories, and quartz furnaces. Example

[0021] In this embodiment, the following weight ratios of raw material components are selected: 80% zirconium dioxide, 19.3% magnesium oxide, and the sum of the weights of yttrium oxide, titanium oxide, calcium oxide, and silicon oxide is 0.7%, of which the weight of silicon oxide is 0.4%, and the weights of yttrium oxide, titanium oxide, and calcium oxide are all 0.1%.

[0022] Step 1: The total mass is 5000g, weigh each component in proportion, mix the components evenly, keep melting at 1900°C for 60 minutes, and then cool to obtain a solid solution raw material with uniform element distribution; Step 2: Grind the element uniformly distributed solid solution raw material obtained in step 1 into a powder with a D50 value of 0.2 to 20 microns; Step 3: Add 3% polyvinyl alcohol (PVA) organic binder to the powder obtained in step 2, and then mix them evenly; Step 4: Place the powder obtained in step 3 in a metal mold, and perform cold isostatic pressing for 20 seconds at a pressure of 600 tons to obtain an initial embryo; Step 5: Add the initial body obtained in step 4 to the curve temperature controller in the electromagnetic induction heating equipment, heat it to 1950°C at 320°C / h at room temperature within 5 hours, maintain the temperature at 1950°C for 2 hours, and then reduce it from 1950°C to room temperature at 320°C / h within 6 hours to obtain a high zirconium brick body; Step 6: Grind and trim the brick body obtained in step 5 to obtain a high-zirconium brick sample.

[0023] Element distribution detection of high zirconium brick samples The high zirconium brick samples prepared in Example 1 were commissioned to a German professional testing agency to test their element distribution. Figure 2 This is a microscopic image of a high-zirconium brick sample. The areas indicated by the white arrows can be clearly seen. These areas show dense and highly dispersed particle distribution. These particles are mainly zirconium dioxide (ZrO2). The ZrO2 particles are cleverly embedded in the matrix material to form a tight and stable combination, ensuring the stable existence of ZrO2 particles in the matrix and effectively avoiding the problem of stable phase destabilization rate. It not only enhances the overall strength and toughness of high-zirconium bricks, but also broadens the application prospects of monoclinic zirconium dioxide crystals.

[0024] Thermal shock and heat penetration practice and testing The high zirconium bricks prepared in Example 1 were subjected to thermal shock and thermal penetration tests using a box-type high-temperature furnace FM1800. First, the high zirconium bricks were trimmed to a length of 320 mm, a width of 310 mm, and a thickness of 70 mm. One side of the high zirconium bricks was heated to 1600°C at 40°C / h within 40 hours. The high zirconium bricks were then kept at 1600°C for 4 hours, and the other side was exposed to room temperature. The temperature of the other side exposed to room temperature was tested to evaluate its thermal shock performance and thermal penetration performance. Figure 3 The following table 1 shows the temperature change of the other side exposed to room temperature during the heating process of one side of the high zirconium brick, and whether there are cracks on the surface.

[0025] Table 1 Temperature change statistics The thermal shock process of this experiment was from room temperature 29 degrees to 1600 degrees, which took 40 hours and was kept warm for 4 hours. During the heating process, there was no abnormal change in the inner and outer surfaces of the high zirconium bricks, and no cracks were found. When the high temperature in the furnace was 1600℃, the other side of the high zirconium brick was exposed to the air and detected to be 600℃. The heat penetration temperature difference was 1000℃, reaching a temperature decrease of 14℃ per 1 mm. It has excellent thermal shock resistance and good heat penetration temperature decrease performance.

[0026] Linear expansion test The high zirconium brick samples prepared in Example 1 were commissioned to the National Refractory Quality Inspection and Testing Center for linear expansion testing. Figure 4 According to the test report, the linear expansion rate of high zirconium bricks is a continuous rising process of 0.02% to 0.38% at 50~600℃, a continuous decreasing process of 0.36%~0.22% at 650~1000℃, and 0.73% at 1400℃; under the same conditions, the linear expansion rate of cast AZS 41#100~1000℃ is an increasing 4.23~0.81%; from the comparative data of high zirconium bricks and cast AZS 41# in Table 2 below, the linear expansion rate of high zirconium bricks at the use temperature is almost the same as that of AZS41#, but the probability of cracks in the preheating process and thermal shock process is low, ensuring the safety of the kiln baking process. Table 2 Comparison of linear expansion data Bubble release test The high zirconium brick samples prepared in Example 1 were commissioned to the National Building Materials Industry Refractory Product Quality Supervision and Inspection Test Center for bubble precipitation testing. Figure 5-6 The test report shows that the bubble precipitation rate of high zirconium bricks at 1300℃ is 0; the bubble precipitation rate at 1500℃ is 0.1; Table 3 is the comparison data of bubble precipitation rate of high zirconium bricks, AZS41 and cast 95. From the data analysis of the National Inspection Center over the years, the bubble precipitation rate of cast AZS is 1-1.2 (different differences are caused by element segregation sampling sites, and the long-term use gradually increases due to glass phase seepage factors in the later period); the bubble precipitation rate of cast 95 high zirconium is 26.50 (in the early stage, the volatilization of carbon retention leads to excessive release, which will gradually decrease in the later period); from the comparative data, high zirconium bricks have a good suppression of bubble defects caused by glass kiln materials, because its elements and density are uniform, and there is no factor of phase structure change, so it is always an extremely low bubble precipitation data and remains stable. High Zirconium Brick Samples ASZ41# Melting Casting 95 1300℃ 0 1~1.2 26.5 1500℃ 0.1 Untested Untested

[0027] Table 3 Comparison data of bubble precipitation rate Corrosion resistance test In this test, the crucible made of the high zirconium brick sample prepared in Example 1 was used to conduct a comparative experiment on the corrosion resistance of a 41# zirconium corundum brick crucible and a 95# fused cast high zirconium brick crucible. High lead glass (corrosive medium) was added to the crucible. The test method was a static crucible method. The experimental temperature was 1600°C and the temperature was kept for 36 hours. Figure 7 c It can be seen that silicon oxide is precipitated inside the 41# zirconium corundum brick crucible, and glass penetrates into the brick surface and crucible holes to form honeycomb holes; Figure 7b. The 95# high zirconium brick has a 1mm expansion hole at the liquid surface, and the color changes to a depth of about 5mm inside the brick, and the remaining glass is turbid, which may be due to component replacement; the crucible high zirconium brick made of the high zirconium brick sample prepared in Example 1 has a 0.5mm expansion hole at the liquid surface (such as Figure 7 a), there is an obvious color change at the contact position with high-lead glass, and the glass is relatively transparent, indicating that the high-zirconium bricks prepared in this embodiment have excellent corrosion resistance.

[0028] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A high zirconium brick, characterized in that: The high zirconium bricks include the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% alumina, and 0.5% to 4.5% by weight of yttrium oxide, titanium oxide, magnesium oxide, calcium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% magnesium oxide, and 0.5% to 4.5% by weight of yttrium oxide, titanium oxide, calcium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% calcium oxide, and 0.5% to 4.5% by weight of magnesium oxide, yttrium oxide, titanium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% chromium oxide, and 0.5% to 4.5% by weight of calcium oxide, magnesium oxide, yttrium oxide, titanium oxide, and silicon oxide; Or the high zirconium brick comprises the following components by weight percentage: 65% to 99% zirconium dioxide, 0.5% to 30.5% beryllium oxide, and 0.5% to 4.5% by weight of calcium oxide, magnesium oxide, yttrium oxide, titanium oxide, and silicon oxide.

2. A process for preparing high zirconium bricks as claimed in claim 1, characterized in that: The preparation process comprises the following steps: Step 1, weigh each component, mix them evenly, react at 1800°C to 3000°C for at least 45 minutes to form a molten liquid or solid phase structure, and cool to obtain a solid solution raw material; Step 2: Grind the solid solution raw material obtained in step 1 into a powder with a D50 value of 0.2 to 100 microns; Step 3: Add 0.1-5% organic binder or inorganic binder to the powder obtained in step 2 and mix well; Step 4: placing the powder obtained in step 3 in a mold, and pressing and molding at a pressure of not less than 500 tons for at least 15 seconds to obtain an initial embryo; Step 5: Heat the initial body obtained in step 4 from room temperature to 1600-1950°C by a temperature control heating device within at least 5 hours, and keep it at not less than 1600°C for at least 1 hour, and then cool it to room temperature within at least 5 hours to obtain a high zirconium brick body; Step 6: Grind and trim the brick body obtained in step 5 to obtain high-zirconium bricks.

3. The preparation process according to claim 2, characterized in that: In the step 1, the mixed components are melted at 1800°C-3000°C for at least 45 minutes and cooled to obtain a solid solution raw material with uniformly distributed elements; or the mixed components are sintered at a high temperature of 1800°C-3000°C by liquid phase reaction for at least 60 minutes and cooled to obtain a solid solution raw material with uniformly distributed elements.

4. The preparation process according to claim 2, characterized in that: In the step three, the organic binder is selected from at least one of polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyacrylamide (PAM), polyimide adhesive, epoxy adhesive, phenolic resin adhesive, and urea-formaldehyde resin adhesive; the inorganic binder includes but is not limited to paraffin wax and wood ash.

5. The preparation process according to claim 2, characterized in that: The powder obtained in step 3 is placed in a mold, and is formed by cold isostatic pressing at a pressure of 500-10,000 tons or by a press machine at a pressure of not less than 500 tons, and is maintained for at least 15 seconds to obtain an initial embryo body.

6. The preparation process according to claim 2, characterized in that: The molds include but are not limited to rubber molds, polyurethane molds, and metal molds.

7. The preparation process according to claim 2, characterized in that: In the step 5, the temperature control and heating equipment adopts a programmable temperature controller, and the starting temperature is set to room temperature, the heating rate is 320-390°C / h, the heating time is at least 5h, the end temperature is 1600-1950°C, and the insulation time is at least 1h.

8. The preparation process according to claim 7, characterized in that: Temperature control heating equipment includes but is not limited to electric heating equipment, electromagnetic induction heating equipment, vacuum heating equipment, protective atmosphere heating equipment, gas heating equipment, plasma heating equipment, and microwave heating equipment.

9. The preparation process according to claim 2, characterized in that: The cooling annealing in step 5 adopts a programmable temperature controller, sets the starting temperature to the furnace temperature, the cooling rate to 390-320° C. / h, the cooling time to at least 5 hours, and the end temperature to room temperature.

10. A high zirconium brick as claimed in any one of claim 1 is used to make various key ceramic products for glass kilns, including but not limited to: crucibles for special glass, high zirconium ceramic stirring paddles, high zirconium ceramic bricks, high zirconium drawing crucibles, high zirconium special-shaped accessories, and quartz furnaces.

Citation Information

Cited By

  • High zirconia brick, and preparation process and use thereof

    EP4741364A1